Cervical cancer screening in low-resource settings: a smartphone image application as an alternative to colposcopy - Gallay C; Girardet A; Viviano M; Catarino R; Benski AC; Tran PL; Ecabert C; Thiran JP; Vassilakos P; Petignat P (Dove Medical Press, 2017)
Caroline Gallay,1,* Anne Girardet,1,* Manuela Viviano,2 Rosa Catarino,2 Anne-Caroline Benski,2,3 Phuong Lien Tran,2,4 Christophe Ecabert,5 Jean-Philippe Thiran,5 Pierre Vassilakos,6 Patrick Petignat2 1Faculty of Medicine, University of Geneva, Geneva, Switzerland; 2Department of Gynecology and Obstetrics, Geneva University Hospitals, Geneva, Switzerland; 3Department of Gynecology and Obstetrics, Saint Damien Healthcare Centre, Madagascar; 4Department of Gynecology and Obstetrics, Reunion University Hospitals, Reunion Island, France; 5Signal Processing Laboratory (LTS5), Ecole Polytechnique Fédérale de Lausanne (EPFL), Lausanne, Switzerland; 6Geneva Foundation for Medical Education and Research, Geneva, Switzerland *These authors have contributed equally to the work Background: Visual inspection after application of acetic acid (VIA) and Lugol’s iodine (VILI) is a cervical cancer (CC) screening approach that has recently been adopted in low- and middle-income countries (LMIC). Innovative technologies allow the acquisition of consecutive cervical images of VIA and VILI using a smartphone application. The aim of this study was to evaluate the quality of smartphone images in order to assess the feasibility and usability of a mobile application for CC screening in LMIC.Methods: Between May and November 2015, women aged 30–65 years were recruited in a CC screening campaign in Madagascar. Human papillomavirus-positive women were invited to undergo VIA/VILI assessment. Pictures of their cervix were taken using a Samsung Galaxy S5 with an application called “Exam”, which was designed to obtain high-quality images and to classify them in the following sequence: native, VIA, VILI and posttreatment. Experts in colposcopy were asked to evaluate if the quality of the pictures was sufficient to establish the diagnosis and to assess sharpness, focus and zoom.Results: The application use was simple and intuitive, and 208 pictures were automatically classified and recorded in the patient’s file. The quality was judged as adequate for diagnosis in 93.3% of cases. The interobserver agreement was κ =0.45 (0.23–0.58), corresponding to a moderate agreement on the common scale of kappa values.Conclusion: This smartphone application allows the acquisition of good quality images for VIA/VILI diagnosis. The classification of images in a patient database makes them accessible to on- and off-site experts, and allows continuous clinical education. Smartphone applications may offer an alternative to colposcopy for CC screening in LMIC. Keywords: visual approach, cervical cancer screening, human papillomavirus, HPV, smartphone, mobile health